P07.01 Mycoplasma genitalium testing pattern and infection rates over a six-year period in melbourne, australia. (13th September 2015) - Tabrizi, SN; Costa, AM; Marceglia, A; Machalek, DA; Bradshaw, CS; Chen, M; Fairley, CK; Garland, SM
Abstract : Introduction: Mycoplasma genitalium (Mg) is an emerging sexually transmitted pathogen with a strong association with urethritis, cervicitis and pelvic inflammatory disease. Detection of this bacterium using molecular assays has been limited due to lack of readily available commercial assays. However, in house 16S rRNA gene qPCR assays have been in use at the laboratory located at the Royal Women's Hospital, in Melbourne Australia for detection of Mg since 2009. The aim of this study was to analyse Mg testing patterns and infection rates over this 6 year period. Methods: We analysed overall detection rates and site-specific positivity in clinical specimens received for testing for Mg between 1 January 2009 and 31 December 2014 from clinics at the Royal Women's Hospital and Melbourne Sexual Health Centre. Results: A total of 46, 112 specimens were tested for Mg; 2, 853 (6.2%) samples were tested in 2009 with an increasing trend to 13, 133 (28.5%) in 2014 (p-trend <0.001). In total 54.7% were urine samples, 37.7% vaginal/cervical swabs and 7.6% were anal, urethral or from other non-specified sites. Overall positivity across all samples was 4.5% (95% CI: 4.3–4.7) without any significant change per annum (p-trend = 0.206). Overall, Mg detection rate was highest in urethral (9.0%, 95% CI: 6.7–11.7) and anal swabs (8.8%, 95% CI 6.8–11.1) followed by urine (5.8%, 95% CI: 5.5–6.7) and cervical/vaginal samples (2.6%, 95% CI: 2.4–2.8) (p < 0.001). A significant increase in positivity was observed in anal swabs, from 2.5% in 2009 to 12.7% in 2014 (p-trend = 0.005). Conclusion: Increased testing for Mg by qPCR has resulted in detection and treatment of over 2000 infections since 2009 in Melbourne, Australia and highlights Mg as an important sexually transmitted infection. Increase in detection of Mg in anal swabs also highlights the importance of rectal testing in symptomatic males. Disclosure of interest statement: No disclosure to declare.